Composite dowels as shear connectors for composite beams – background to the German technical approval. Issue 2 (May 2016) - Feldmann, Markus; Kopp, Maik; Pak, Daniel
Abstract: Composite dowels are known as powerful shear connectors in steel‐concrete composite girders. They are being used more and more in practice, especially for prefabricated composite bridges. Compared with headed studs, they provide increased strength. They also exhibit good deformation capacity even in high‐strength concrete. Further, their use in steel sections without an upper flange is very simple. However, a lack of standards for composite dowels with the economic clothoid and puzzle shapes has led to hesitations regarding applications, which is often due to delays in the approval process. Hence, the aim of the recently finished German research project P804 funded by FOSTA, the Research Association for Steel Application, was to solve unanswered questions concerning these innovative shear connectors and to prepare a national technical approval18 available for any design office or construction company. This paper describes the technical rules derived for ultimate and fatigue limit states, the structural design principles and instructions for production and construction, and provides further background information.